Species wise composition of some food fishes - Joshi, Promod (Journal of Experimental Sciences, 2012)
Species wise composition of some food fishes in Nanak sagar reservoir has been studied for two year 2008- 2009.The catch of fishes species fluctuated between 1142.0kg an 4% to 6898.0kg and 28% and the total number of fishes fluctuated between 501.0kg and 2%to 3940.0kg an 20%in the year 2008 while in the second year 2009 the catch species fluctuated between 95.0kg and 4% to 8142.0kg and 30% and total number of species fluctuated between 532.0kg and 4% to 3630.0kg and 29%in reservoir.